2021
DOI: 10.1111/nyas.14728
|View full text |Cite
|
Sign up to set email alerts
|

An update on current treatment strategies for laryngopharyngeal reflux symptoms

Abstract: Laryngopharyngeal reflux (LPR) is a syndrome caused by reflux of gastric contents into the pharynx or larynx, which leads to symptoms of throat clearing, hoarseness, pain, globus sensation, cough, excess mucus production in the throat, and dysphonia. LPR is a challenging condition, as there is currently no gold standard for diagnosis or treatment, and thus this presents a burden to the healthcare system. Strategies for treatment of LPR are numerous. Medical therapies include proton pump inhibitors, which are f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 74 publications
(200 reference statements)
0
25
0
Order By: Relevance
“…Further, an enhanced brain-larynx interaction can coexist with true LPR, just as patients with GERD or oesophageal motility disorders can have concomitant oesophageal hypersensitivity. 94 For example, in one study, researchers evaluated the Oesophageal Hypervigilance and Anxiety Scale (EHAS) in patients with chronic laryngeal symptoms and identified similarly elevated EHAS scores across patient groups with or without objective GERD. 18 Similarly, Wong et al 95 identified increased oesophageal hypervigilance and symptom-specific anxiety in patients with both GERD and LPR symptoms, LPR predominant and GERD predominant symptoms when compared to controls, and once again, reflux burden did not differ across groups.…”
Section: Disorders Of Brain-larynx Interaction Laryngeal Hypersensiti...mentioning
confidence: 99%
See 2 more Smart Citations
“…Further, an enhanced brain-larynx interaction can coexist with true LPR, just as patients with GERD or oesophageal motility disorders can have concomitant oesophageal hypersensitivity. 94 For example, in one study, researchers evaluated the Oesophageal Hypervigilance and Anxiety Scale (EHAS) in patients with chronic laryngeal symptoms and identified similarly elevated EHAS scores across patient groups with or without objective GERD. 18 Similarly, Wong et al 95 identified increased oesophageal hypervigilance and symptom-specific anxiety in patients with both GERD and LPR symptoms, LPR predominant and GERD predominant symptoms when compared to controls, and once again, reflux burden did not differ across groups.…”
Section: Disorders Of Brain-larynx Interaction Laryngeal Hypersensiti...mentioning
confidence: 99%
“…Secondly, most studies evaluating LPR use various diagnostic modalities, such as laryngoscopy and symptombased questionnaires, which are not recommended as diagnostic modalities in patients presenting with chronic laryngeal symptoms. 94 Furthermore, even when ambulatory reflux monitoring is used, it is unclear what type of reflux monitoring system should be used (prolonged wireless reflux monitoring or 24 h impedance-pH monitoring) nor if traditional pH and reflux thresholds for GERD can be applied to patients with chronic laryngeal symptoms. 14,94 Consequently, it is reasonable to reserve a PPI trial for patients with chronic laryngeal symptoms and concomitant GERD symptoms and perform up-front reflux testing in those with isolated laryngeal symptoms.…”
Section: Acid-suppressive Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The medical treatment of P-LPR was long-standing based on the use of histamine (H2) blockers or PPIs. PPIs and histamine (H2) blockers bind irreversibly to active proton pumps and increase the pH of gastroesophageal and esophago-pharyngeal reflux events without influencing the number and duration of events [ 4 , 99 ]. In adults, the superiority of PPIs over placebo is not demonstrated [ 100 ].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…By definition, LPR is a pharyngeal inflammatory disease directly or indirectly caused by gastroduodenal contents reflux, which could lead to symptoms of morning hoarseness and nocturnal coughing, sore throat, excessive mucus production, and foreign body sensation in the pharynx 4,5 . Current treatments for LPR mainly include lifestyle modifications and pharmacological treatments, such as proton pump inhibitors (PPIs) 6,7 …”
mentioning
confidence: 99%